Tradition and Modernity in Neil Gaiman’s Prose: American Gods and Good Omens - Taquet, David (Contrasts in humanities: literature, language, culture, 2023)
Structuring the stories of Neil Gaiman’s American Gods (2001) and Good Omens (1990), which he wrote in collaboration with Terry Pratchett, the contrasts between tradition and modernity are declared on several levels: the relationship between deities and technological advances, the preservation of traditional values in the idyllic small-town setting, as well as Neil Gaiman’s willingness to modernize the original works to fit current societal values. These apparent contrasts sometimes find a peaceful resolution, offering readers a welcome synthesis that encourages acceptance of modernity despite the sacrifices that must be made.